2013
DOI: 10.1109/tmech.2012.2210239
|View full text |Cite
|
Sign up to set email alerts
|

An Origami-Inspired Approach to Worm Robots

Abstract: Abstract-This paper presents an origami-inspired technique which allows the application of 2-D fabrication methods to build 3-D robotic systems. The ability to design robots as origami structures introduces a fast and low-cost fabrication method to modern, real-world robotic applications. We employ laser-machined origami patterns to build a new class of robotic systems for mobility and manipulation. Origami robots use only a flat sheet as the base structure for building complicated bodies. An arbitrarily compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
184
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 312 publications
(184 citation statements)
references
References 17 publications
0
184
0
Order By: Relevance
“…NiTi coils can achieve displacements that are orders of magnitude greater (>100%) than those of a typical axiallyaligned SMA wire [25], [35]. The combination of high forces, large displacements, simple activation mechanism, low mass, compact form factor and fiber-like aspect ratio make NiTi Fig.…”
Section: Theory and Modeling Of Niti Coil Actuatorsmentioning
confidence: 99%
“…NiTi coils can achieve displacements that are orders of magnitude greater (>100%) than those of a typical axiallyaligned SMA wire [25], [35]. The combination of high forces, large displacements, simple activation mechanism, low mass, compact form factor and fiber-like aspect ratio make NiTi Fig.…”
Section: Theory and Modeling Of Niti Coil Actuatorsmentioning
confidence: 99%
“…Currently, 3-D printing-depositing material directly into a desired structure-is the most common method of this type [1][2][3] . However, an origami-inspired technique has recently been demonstrated that creates three-dimensional structures by folding two-dimensional materials [4][5][6] . This has several advantages over traditional methods: Folding thin sheets into 3-D shapes often requires less material than an equivalent solid structure.…”
Section: Introductionmentioning
confidence: 99%
“…Complimentary theoretical work has proven that folding is in fact capable of achieving a large set of target geometries [8], [9], [10]. Recently, origami inspired folding has also enabled great strides in the fabrication of mm to cm scale robotics [11], [12], [13]. However, fold actuation remains a challenge as these robots often require many hours and/or *The authors gratefully acknowledge support from the National Science Foundation (award numbers CCF-1138967 and EFRI-1240383).…”
Section: Introductionmentioning
confidence: 99%